The Impact of Economic Globalization on The Indonesian Economy - Mardhiyah, Saily (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2023)
Economic globalization is a process of integrating the national economy into the global economic system carried out by TNC, WTO, IMF and World Bank actors. Economic globalization is the increasing economic integration and interdependence of national, regional and local economies throughout the world through the intensification of cross-border movement of goods, services, technology and capital. Globalization causes trade between countries to become freer. This is one of the greatest benefits for nation building. Domestic industries experience reduced trade barriers and have access to wider international markets. Economically, Indonesia depends on international trade, production and finance. Therefore, the Indonesian state is vulnerable to international pressure and globalization. Economic globalization has an impact on national economic laws which must appear as an integration mechanism that can harmonize various internal interests of the nation, national and international interests as well as between sectors of national life. Economically, there is pressure on increasingly competitive trade, multinationalization of production, integration of financial markets and the influx of global capital investment. In facing the impact of economic globalization, the strategy used is to play an active role in the negotiation process with globalization actors and create national economic laws, especially regarding foreign investment, which accommodate global value interests to be utilized for national economic development.